Meta-analysis of uveal melanoma genome-wide association studies identifies novel risk loci and population effect size heterogeneity - Georgia Mies; Noah L. Tsao; Alexandre Houy; Sarah E. Coupland; Helen Kalirai; Asta Försti; Kari Hemminki; Hauke Thomsen; Marc-Henri Stern; Carol L. Shields; Scott M. Damrauer; Katheryn G. Ewens; et al. (HGG Advances)
Summary: Uveal melanoma (UM) is a rare but frequently metastasizing cancer. Genome-wide association studies have identified three common genome-wide significant germline risk loci. Here, we perform a genome-wide association study on 401 new cases and conduct a meta-analysis with three independent previously published cohorts for a total sample size of 2,426 cases. We confirm the three previously identified risk loci and identify four additional genome-wide significant loci. We find that eye pigmentation-decreasing variants are systematically associated with increased UM risk and that selection for lighter pigmentation in the past 5,000 years explains about 73% of the difference in UM incidence between Northern and Southern Europe. We find evidence of effect size heterogeneity at significant loci across cohorts, in particular, a weaker association between eye pigmentation and UM in a Finnish cohort. Finally, we confirm differential effect sizes between uveal melanoma cases with and without loss of chromosome 3, the major determinant of metastatic risk. Our study identifies novel germline risk factors for UM and highlights genetic and environmental heterogeneity in its etiology.